ATTITUDE AND PERCEIVED BEHAVIORAL CONTROL ON INTENTION OF CUSTOMERS IN TAKING DECISIONS TO PURCHASE HOME IN BANK A - Dewi Oktari, Sari; Rinta Suhardi, Agatha (International Journal of Psychosocial Rehabilitation, 2020)
The house is one of the basic human needs that must be met. But house prices continue to soar every year, making it rare for people to be able to buy a house in cash. Rising house prices can be caused by several factors; one factor is the market mechanism. The purpose of this study was to determine the influence of attitude and perceived behavioral control on the intention of Bank A customers in making home purchase decisions. And to find out the attitude and perceived behavioral control of Bank A customer intention partially. The research method used is a quantitative research method with a survey approach; the population used is the customer and prospective customers at Bank A. The sample of this study was 100 respondents. The analytical method used is multiple regression analysis and hypothesis testing. The results of the analysis show that attitude influences intention, while perceived behavioral control has no effect on attention.